PENGARUH PENAMBAHAN KOMPOSISI ABU BAMBU TERHADAP SIFAT FISIK KERAMIK BERBAHAN DASAR KAOLIN - Kirana, Rizka Fatimah; Budi, Agus Setyo; Budi, Esmar; Sahar, Md. Rahim; Samah, Khamisah Abu (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Utilization of bamboo waste, especially ash from the combustion is rarely found as well as ceramic tile that made from agricultural waste. This experiment of making ceramics from agrowaste-bamboo used various composition. The composition of this making the ceramics is 30%, 40%, 50% and 60% of bamboo ash. The purpose of this study is to determine the effect of bamboo ash composition on the physical characteristics of ceramic which is called density. The bamboo ash with a size of 100 microns was selected for testing. Sintering technique carried out at a temperature of 700Â°C to this kaolin based ceramic. Testing is done by using the Archimedes method. The addition of bamboo ash composition than caolin to produce lower density structures with the highest value 2.261885321 g/cmá¶Ÿ and the lowest is 2.195299124 g/cmá¶Ÿ. These results indicate that the addition of bamboo ash composition having an effect on the physical characteristics of ceramics. Keywords: Ceramics, Agrowaste, Bamboo Ash, Sintering, Kaolin.